2005
DOI: 10.1109/tmi.2005.853240
|View full text |Cite
|
Sign up to set email alerts
|

Standardized evaluation methodology for 2-D-3-D registration

Abstract: In the past few years, a number of two-dimensional (2-D) to three-dimensional (3-D) (2-D-3-D) registration algorithms have been introduced. However, these methods have been developed and evaluated for specific applications, and have not been directly compared. Understanding and evaluating their performance is therefore an open and important issue. To address this challenge we introduce a standardized evaluation methodology, which can be used for all types of 2-D-3-D registration methods and for different appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(120 citation statements)
references
References 34 publications
3
115
1
1
Order By: Relevance
“…When the absolute parameter range is (12 o , 12mm), the average CPU time tested on a 3.0 GHz Pentium machine was 26.7 seconds. It was found that the capture range of the PW-MRF-VA-MI was much larger than those reported in [7] and in [14], although the attained accuracy was lower than that reported in [14]. This might be explained by the large inter-slice distance (2.5 mm in this work vs. 0.31 mm in [14]) and the region outliers in the X-ray images.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…When the absolute parameter range is (12 o , 12mm), the average CPU time tested on a 3.0 GHz Pentium machine was 26.7 seconds. It was found that the capture range of the PW-MRF-VA-MI was much larger than those reported in [7] and in [14], although the attained accuracy was lower than that reported in [14]. This might be explained by the large inter-slice distance (2.5 mm in this work vs. 0.31 mm in [14]) and the region outliers in the X-ray images.…”
Section: Resultscontrasting
confidence: 60%
“…We then performed the registration starting from these perturbed positions and counted the success rate. Using a method similar to that reported in [14], we regarded a registration as successful if the mean target registration errors (mTRE) evaluated on the fiducial markers was smaller than 1.5 mm . The capture range was defined as the average of the initial mTRE when a 95% success rate is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 Mean rendering times (in ms) and their standard deviations (SD) for 27000 renderings using GPU based wobbled splat rendering and GPU based ray casting including several optimization techniques for them. Two reference datasets available to the public [36,37] were used for this validation. Table 2 Measured times including standard deviations for the overall registration process.…”
Section: Resultsmentioning
confidence: 99%
“…The most important case is 2D/3D image registration of digitally rendered radiographs (DRRs) and X-ray images taken with a known projection geometry [68,[76][77][78][79][80][81][82]. This is widely used in image-guided surgery and image-guided radiotherapy.…”
Section: Intensity-based Image Registrationmentioning
confidence: 99%